(untitled) (Applied Biological Research, 2016)
The present study was aimed to assess the response of rainfed maize to various fertility levels and weed management practices under temperate Kashmir conditions. The field experiment consisted of 3 fertility levels of NPK viz., 60:40:20, 75:50:30 and 90:60:40, N:P2O5:K2O kg ha-1) and 4 weed management practices viz., no weeding, two hand weeding 20 and 50 days after sowing (DAS), atrazine @ 1.0 kg a.i. ha-1 (as pre emergence) + one hand weeding 20 DAS, and atrazine @ 1.0 kg a.i. ha-1 (pre-emergence) + isoprotron @ 1.0 kg a.i. ha-1 (post-emergence). The results revealed that fertility levels of 90:60:40 and 75:50:30 (NPK) were at par and showed significant increase in cob length, cobs plant-1, grains cob-1, 100-seed weight, grain yield, biological yield and stover yield as against fertility level of 60:40:20 NPK. However, the number of rows cob-1 and cob diameter showed significant improvement with increase in fertility level. Increase in fertility level from 60:40:20 to 75:50:30 NPK significantly enhanced harvest index but further addition caused significant decrease. Weed management practices of atrazine as pre emergence application + one hand weeding at 20 DAS was at par with atrazine as pre-emergence + isoprotron as post-emergence application treatment and both showed significant improvement in all yield contributing characters over no weeding and 2 hand-weedings at 20 and 50 days DAS. Both grain and stover yields were significantly higher with atrazine as pre-emergence application + 1 hand weeding at 20 DAS over hand weeding on 20 and 50 DAS and no weeding.